Hydroxycinnamic acids and their derivatives in broa, a traditional ethnic maize bread - Bento‐Silva, Andreia (2021)
This research was funded by EUROPEAN UNION'S SEVENTH FRAMEWORK PROGRAMME for research, technological development and demonstration under grant agreement number 245058, by FUNDACAO PARA A CIENCIA E TECNOLOGIA and PORTUGAL 2020 to the Portuguese Mass Spectrometry Network, grant number LISBOA-01-0145-FEDER-402-022125 and by FUNDACAO PARA A CIENCIA E TECNOLOGIA through IF/01337/2014 FCT Investigator contract (MCVP) and research unit GREEN-IT (UID/Multi/04551/2020).